Perfluorooctanoic acid (PFOA) exposure in relation to the kidneys: A review of current available literature - Liu, Dongge; Yan, Shuqi; Wang, Pingwei; Chen, Qianqian; Liu, Yanping; Cui, Jiajing; Liang, Yujun; Ren, Shuping; Gao, Ying (Frontiers in Physiology, 2023)
Perfluorooctanoic acid (PFOA) is an artificial and nondegradable chemical，it is widely used due to its stable nature. It can enter into human body through food, drinking water, inhalation of household dust and contact with products containing perfluorooctanoic acid, and accumulate in the human body, causing potential harmful effects on human health. Based on the biodegradability and bioaccumulation of perfluorooctanoic acid in human body, people are increasingly concerned about the adverse effects of perfluorooctanoic acid exposure on kidneys. Research shows that kidney is the main accumulation organ of PFOA，PFOA can cause nephrotoxicity and produce adverse effects on kidney function, but the exact mechanism is still unknown. In this review, we summarized the relationship between PFOA exposure and kidney health，evaluated risks more clearly, and provided a theoretical basis for subsequent research.